2022
DOI: 10.3390/healthcare10112243
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Barriers That Cause Unmet Healthcare Needs in the Life Cycle of Adulthood and Their Policy Implications: A Need-Selection Model Analysis of the Korea Health Panel Survey Data

Abstract: Using 68,930 observations selected from 16,535 adults in the Korea Health Panel Survey (2014–2018), this study explored healthcare barriers that prevent people from meeting their healthcare needs most severely during adulthood, and the characteristics that are highly associated with the barrier. This study derived two outcome variables: a dichotomous outcome variable on whether an individual has experienced healthcare needs, and a quadchotomous outcome variable on how an individual’s healthcare needs ended. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 110 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…This information can be used to develop targeted and effective interventions to improve access to health care services. Even in the context of universal health insurance coverage, unmet needs persist when financial or non-financial barriers prevent individuals from seeking necessary health care [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This information can be used to develop targeted and effective interventions to improve access to health care services. Even in the context of universal health insurance coverage, unmet needs persist when financial or non-financial barriers prevent individuals from seeking necessary health care [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is because UHN can identify barriers to healthcare access that might not be determined by other measures from the healthcare services supply side, such as the presence of healthcare facilities, outpatient visits, and hospital admission rates (Chen & Hou, 2002;Jung & Ha, 2021;Meemon & Paek, 2019;Mitrašević et al, 2020;Sanmartin et al, 2002). Past research has shown that UHN can arise from factors related to the healthcare system, including the availability and quality of services provided by healthcare facilities (Chung, 2022;Hwang, 2018;Marrone, 2007), as well as from population characteristics, such as socioeconomic and demographic status (Åhs et al, 2012;Allin et al, 2010;Bryant et al, 2009;Lee et al, 2015;Stevens & Gillam, 1998).…”
Section: Unmet Healthcare Needsmentioning
confidence: 99%